X Ray Photon Correlation Spectroscopy for the study of polymer dynamics. (August 2016) - Nogales, Aurora; Fluerasu, Andrei
Graphical abstract: Highlights: X Ray Photon Correlation Spectroscopy, XPCS, is a novel technique developed for the study of slow dynamics in condensed matter. The technique is similar to photon correlation spectroscopy, where the temporal variations of the speckle pattern due to scattering by the material of a coherent source are analyzed. XPCS has been developed in third generation synchrotron but its importance will grow in higher flux sources. The results from these techniques and future perspectives in the field of polymer science are discussed here. Abstract: X Ray Photon Correlation Spectroscopy, XPCS, is a novel technique developed for the study of slow dynamics in condensed matter. The principle of this technique is based on the time variations of the speckle pattern originated by the scattering of coherent light from a material with spatial inhomogeneities. Although laser photon correlation spectroscopy was long established, XPCS has only been possible with the advent of new synchrotron radiation X-ray sources that can provide sufficient coherent flux. The results from these techniques and future perspectives in the field of polymer science are discussed here.